Pengaruh kecerdasan emosional, kecerdasan intelektual dan minat belajar terhadap tingkat pemahaman akuntansi - Yolla Yorika; Azwir Nasir; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study examined the effects of emotional intelligence, intellectual intelligence, and behavioral learning towards the level of understanding of accountancy.The sample of this studied is 25 students of Riau University, 25students of Riau Islamic University, 25 students of UIN Sultan Syarif Qasim and 25 students of Lancang Kuning University. Analytical techniques used to perform the hypothesis testing is purposive sampling with nonprobability sampling types. Data are analyzed using multiple regression analysis method using SPSS(Statistical Product and Service Solution) 17 version.The results showed that the emotional intelligence had a effect to the level of understanding of accountacy looked from thitung (2,952) >ttabel (1,984) with signification values 0,004 (< 0,05). For intellectual intelligence variable had a effect to the level of understanding of accountacy looked from thitung (22,653) > ttabel (1,984) with signification values 0,000 (< 0,05). Behavioral learning had a effect the level of the level of understanding of accountacy looked from thitung (22,449)>ttabel (1,984) with signification values 0,000 (<0,05). The adjusted values R2 0,906 with 90,6 % ratios.Key words : emotional intelligence, intellectual intelligence,behavioral learning, understanding of accountancy.